DIVERSITY OF BANANA VARIETIES (Musa sp.) IN PASRUJAMBE DISTRICT, LUMAJANG REGENCY - Novitalia Novitalia; Ika Lia Novenda; Pujiastuti Pujiastuti (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
The banana plant is a plant that grows a lot in Southeast Asia so it is one of the plants that have important economic significance in Indonesia. One of the banana production centers is in Lumajang Regency, precisely in Pasrujambe District. The diversity of banana varieties in Pasrujambe District is still not widely known by the community so that the community itself has not been able to determine a clear standard of banana diversity including because bananas also receive less attention from the government and supervision related to aspects of cultivation, breeding activities, and conservation regarding the preservation of banana germplasm. This became the basis for exploring the diversity of banana variety of data collection in the Pasrujambe District, Lumajang Regency. This research was conducted at the centers of banana collectors located in the District of Pasrujambe, Lumajang Regency in December 2019-February 2020. Taking samples by taking bananas based on the morphology of bananas. The sample obtained can be directly identified (identification of bananas assisted by the Pasrujambe Agricultural Office) using interview and observation methods. Then the results obtained are calculated diversity level using the Shannon-Wienner diversity index formula. The results of this study were found 6 banana varieties, namely mas kirana, grand semeru varieties, milk varieties, ambon varieties, king varieties, and kepok varieties which were scattered in several collectors centers in Pasrujambe District. The level of diversity of banana varieties in the Pasrujambe District Lumajang Regency is classified as moderate with a value of 1, 566.